Predictive value of the Groningen Frailty Indicator for treatment outcomes in elderly patients after head and neck, or skin cancer surgery in a retrospective cohort. (October 2015) - Bras, L.; Peters, T.T.A.; Wedman, J.; Plaat, B.E.C.; Witjes, M.J.H.; van Leeuwen, B.L.; van der Laan, B.F.A.M.; Halmos, G.B.
<x xml:space="preserve">Abstract</x> Objectives Careful selection of patients eligible for extensive head and neck cancer surgery is extremely important. A reliable predictor for postoperative outcomes in the vulnerable elderly population is not yet available. The concept of frailty describes a clinical state of increased vulnerability and can be assessed using frailty tests, such as the Groningen Frailty Indicator. In the current study, the influence of Groningen Frailty Indicator‐measured frailty on clinical outcome was investigated in elderly patients surgically treated for head and neck cancer. Design Retrospective, explorative cohort study. Setting Tertiary referral centre. Participants A total of 90 patients of 65 years and older receiving surgical treatment for head and neck cancer with different primary sites. Main outcome measures The influence of frailty (Groningen Frailty Indicator) on postoperative complications (Clavien–Dindo classification), subjective postoperative experience of both patient and surgeon and survival were analysed. Results A total of 36 patients were considered as frail (40%). Postoperative complications could not be predicted by frailty status. However, the Groningen Frailty Indicator dimension 'health problems' was a significant predictor for postoperative complications (P = 0.020). Unlike age and comorbidity, frailty was associated with a poor subjective patients' experience of the postoperative recovery (P < 0.01). Although not statistically significant, survival analysis showed a worse 5‐year overall survival in the frail group (33%) versus the non‐frail group (74%). Conclusions Analysis of frailty could identify elderly patients who might suffer more than expected during the postoperative period after head and neck cancer surgery. In this study, frailty was not identified as a new predictor of complications after head and neck cancer surgery.